Tindak Pidana Pengancaman Antar Pelajar Melalui Media Sosial (Cyber Bullying) Menurut Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi Dan Transaksi Elektronik (Uu-Ite) - Bayu Shw; Munib Munib; David Cahyadi; Mijan Mijan; Edy Santoso (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Social media is a means that provides features for its users to interact, express, and various experiences, ideas, and thoughts. However, not everyone is free to use social media. Along with the increase in internet access, social media has become one of the means that is often accessed, including by children and adolescents, especially among students. However, parents are encouraged to be more vigilant because social media can affect the lives of children and adolescents. Cyberbullying is intentional behavior to hurt others online. This is a serious problem, especially because adolescents can experience great emotional and psychological impacts due to acts of bullying. The trend of using social networks as a venue for online oppression is increasing. This research aims to analyze the criminal act of intimidation between students that occurs through social media, in the context of Indonesian law regulated in the Electronic Information and Transaction Law (UU ITE) No. 19 of 2016. This research focuses on the form of threats made by students against other students using social media platforms. Through a normative legal approach, this study identifies and evaluates regulations related to cyber bullying, as well as how to apply the ITE Law in cases involving students. This study also discusses efforts to prevent and overcome cyber bullying involving students. With a descriptive research method, the results of this study show that even though the legislation already exists, the implementation of countermeasures against cyber bullying is still experiencing various obstacles.